2019
DOI: 10.1371/journal.pone.0210505
|View full text |Cite
|
Sign up to set email alerts
|

Quantity and quality of image artifacts in optical coherence tomography angiography

Abstract: ObjectiveTo analyze quality and frequency of OCTA artifacts and to evaluate their impact on the interpretability of OCTA images.Design75 patients with diabetic retinopathy (DR), retinal artery occlusion (RAO), retinal vein occlusion (RVO), or neovascular age-related macular degeneration (nAMD) and healthy controls were enrolled in this cross-sectional study in the outpatient department of a tertiary eye care center.MethodsAll participants underwent an OCTA examination (spectral domain OCT Cirrus 5000 equipped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 11 publications
0
76
0
2
Order By: Relevance
“…Also, evaluation of en face retinal maps could avoid projection artifacts misinterpretation. However, a pronounced edema or highly reflective intraretinal structures could produce masking artifacts in underlying layers [ 20 ]. Previous reports noticed the absence of capillaries detection in the areas of retinal cysts [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, evaluation of en face retinal maps could avoid projection artifacts misinterpretation. However, a pronounced edema or highly reflective intraretinal structures could produce masking artifacts in underlying layers [ 20 ]. Previous reports noticed the absence of capillaries detection in the areas of retinal cysts [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we only analyzed SCP, not DCP and choriocapillaries. However, previous studies have shown that projection artifacts may affect quantitative analysis of DCP and choriocapillaries, and Enders et al 34 reported that 75% of deep retina images were shown projection artifacts. Further studies on the changes of DCP and choriocapillaries using projection-resolved OCTA will be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Further longitudinal studies may help to address the question of whether retinal vessel density is altered with age. Second, even subtle ocular movements during imaging can cause significant artifacts that may confound the analysis of the results; appropriate interpretation is needed to acquire a high-quality retinal vascular network image [26].…”
Section: Discussionmentioning
confidence: 99%